Teacher trainees' readiness to use multimedia in classroom - Nordin, Hasniza (Central Queensland University Press, 2008)
This study examined a model of teacher trainees' readiness to use multimedia in the classroom by incorporating constructs from Technology Acceptance Model (TAM). Structural equation modelling analysis supported a model in which perceived usefulness and perceived ease of use positively influenced mediating variables (attitude towards computer) to predict intention to use.